2010
DOI: 10.1177/097380100900400103
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Demand for Life Insurance in an Emerging Economy—India

Abstract: Expenditure (NSHIE), this article attempts to identify determinants of life insurance ownership in the country. An analysis using logistic regression has corroborated that insured households tend to be more prosperous, more educated and more optimistic about future security than non-insured households. Both the level of education and occupation of the chief earner of a household are major determinants of life insurance participation, apart from asset-ownership. Further, households that are more optimistic abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Given that governmental social support is virtually non-existent in many developing countries, consumers are likely to increase their purchases of insurance products to protect against negative life consequences (van Ginneken, 2003;Kakar and Shukla, 2010). Thus, protecting a developing country's at-risk consumers (Andaleeb and Anwar, 1996;Cole et al, 2009;Obalola, 2010;Reza and Iqbal, 2007) from unethical sales practices is important.…”
Section: Discussionmentioning
confidence: 99%
“…Given that governmental social support is virtually non-existent in many developing countries, consumers are likely to increase their purchases of insurance products to protect against negative life consequences (van Ginneken, 2003;Kakar and Shukla, 2010). Thus, protecting a developing country's at-risk consumers (Andaleeb and Anwar, 1996;Cole et al, 2009;Obalola, 2010;Reza and Iqbal, 2007) from unethical sales practices is important.…”
Section: Discussionmentioning
confidence: 99%
“…53 Moreover, it could not trace any evidence of higher LI enrolment by salaried people vis-à-vis self-employed or businessmen, opposing literature. 39 Third , it has correlated with the literature as far as influences of risk and returns on savings and LI enrolment have been concerned, notwithstanding opposite results have also been concurred. The risk-taking propensity of the young has been validated as a good number of respondents have been saving in the MFs and ULIPs in contrast with older who have preferred government-edged safer instruments, correlated with the literature.…”
Section: Introductionmentioning
confidence: 56%
“…[26][27][28][29][30][31][32][33][34][35] Moreover, studies on customer-related aspects such as the buying behaviour about LI, motivators of the LI demand, attitudes towards the LI companies, role of post office saving bank accounts in spreading the LI, dispute settlement mechanisms, understanding rural customers' behaviours and customer satisfaction, preferences and satisfaction levels in changing environment and assaying the Life Insurance of India (LICI)'s success in countering private players' exaggerated advertisements, status, and role of microinsurance have been attempted. [36][37][38][39][40][41][42][43][44] Furthermore, financial illiteracy to lack of trust in insurance products causing India's poor demand for LI have also been identified notwithstanding Indian LI market is considered as the world's most dynamic and innovative microinsurance market. [45][46][47] A careful review has indicated studies on the Indian LI sector have been conducted in last two decades focusing on macro and micro perspectives but literature likely remained scant in answering the research question of whether LI schemes have been perceived as a saving avenue or as a protection tool.…”
Section: Introductionmentioning
confidence: 99%
“…To test the effect of the mentioned variables on life insurance demand in India, measured by density, penetration, first year premium amount and total life insurance fund etc, we confined to Multiple Regression Loglinear Model. According to Ghosh (2013) the most common specification in the studies of the determinants of life insurance demand is the log-linear form used by Kakar and Shukla (2010), Mitra&Ghosh (2010), Sen (2008), Sadhak (2006) and Beck and Webb (2003). The Logarithmic transformation technique allows us to forecast, the volatilities of demand for life insurance.…”
Section: Methodsmentioning
confidence: 99%